Cover Image. Issue 1 (12th May 2021) - Milosa, Fabiola; Critelli, Rosina Maria; Lasagni, Simone; Pivetti, Alessandra; Di Marco, Lorenza; Romagnoli, Dante; Carulli, Lucia; Dituri, Francesco; Mancarella, Serena; Giannelli, Gianluigi; Martinez‐Chantar, Maria‐Luz; Fabris, Luca; et al.
Abstract : The cover image is based on the Original Article PROGNOSTIC SIGNIFICANCE OF HYPOXIC AND METABOLIC GENE PROFILING IN HEPATOCELLULARCARCINOMA by Erica Villa et al., https://doi.org/10.1002/lci2.23 .